2003
DOI: 10.1021/ac035064h
|View full text |Cite
|
Sign up to set email alerts
|

Improved Planar Amperometric Nitric Oxide Sensor Based on Platinized Platinum Anode. 1. Experimental Results and Theory When Applied for Monitoring NO Release from Diazeniumdiolate-Doped Polymeric Films

Abstract: An improved miniature amperometric nitric oxide sensor design with a planar sensing tip (ranging from 150 microm to 2 mm in diameter) is reported. The sensor is fabricated using a platinized platinum anode and a Ag/AgCl cathode housed behind a microporous poly(tetrafluoroethylene) (PTFE; Gore-tex) gas-permeable membrane. Platinization of the working platinum electrode surface dramatically improves the analytical performance of the sensor by providing approximately 10-fold higher sensitivity (0.8-1.3 pA/nM), ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(148 citation statements)
references
References 34 publications
2
146
0
Order By: Relevance
“…S7). The sensitivity of the sensor is 54 mS per 1,000 nM originally, and became 53 mS per 1,000 nM (98%) after 1 week and 47 mS per 1,000 nM (89%) after 3 weeks, which are comparable to the electrochemical sensors 7,12 . This signal drift is probably because of nonspecific surface adsorptions, and the stability of the device may be further improved through storage in a controlled environment.…”
Section: Fabrication and Characterization Of Graphene-hemin Sensorsmentioning
confidence: 57%
See 1 more Smart Citation
“…S7). The sensitivity of the sensor is 54 mS per 1,000 nM originally, and became 53 mS per 1,000 nM (98%) after 1 week and 47 mS per 1,000 nM (89%) after 3 weeks, which are comparable to the electrochemical sensors 7,12 . This signal drift is probably because of nonspecific surface adsorptions, and the stability of the device may be further improved through storage in a controlled environment.…”
Section: Fabrication and Characterization Of Graphene-hemin Sensorsmentioning
confidence: 57%
“…Electrochemical NO-sensing electrodes allow for real-time detection of NO with high sensitivity and selectivity [11][12][13][14] . However, as the signal amplitude and sensitivity of electrochemical sensors are generally proportional to the electroactive surface area of the electrodes 13 , it is often difficult to simultaneously achieve high sensitivity and high-spatial resolution.…”
mentioning
confidence: 99%
“…Therefore, further surface modification with permselective membranes is required to achieve the desired selectivity for NO via size exclusion or electrostatic repulsion [4]. Indeed, several polymeric materials have been evaluated as gaspermeable or permselective membranes including nafion, collodion, polycarbazole, o-and m-phenylenediamine, poly(tetrafluoroethylene), cellulose acetate, and multilayer hybrids of these polymers [27,[30][31][32][33][34][35][36]. In particular, Shin et al reported that sol-gel-derived electrochemical sensors showed good sensitivity and selectivity for NO detection [17,27].…”
Section: Direct Methods (Nitric Oxide Sensor)mentioning
confidence: 99%
“…100 The porous membrane effectively discriminated against potentially interfering nitrite ions, and the platinization was responsible for a 10-fold lower detection limit down to 1 nM), higher sensitivity and improved stability compared to bare platinum electrodes. This type of sensor was later modified with a thin hydrophilic polyurethane film containing catalytic copper sites that mediated the decomposition of S-nitrosothiols to NO for the fabrication of an electrochemical sensor for S-nitrosothiols.…”
Section: Voltammetric Sensors: Analytes Of Interestmentioning
confidence: 99%